A Hybrid Approach to the Surgical Treatment of a Large Prolapsed Pedunculated Submucous (Nascent) Leiomyoma: Transvaginal Myomectomy Followed by Operative Hysteroscopy - Bekir Sıtkı İsenlik; Orkun Han; Zeynep Ozturk Inal; Hasan İnal (Muğla Sıtkı Koçman Üniversitesi Tıp Dergisi, 2026)
Uterine leiomyomas are the most common benign pelvic tumors in women. In rare cases, submucous leiomyomas may prolapse through the cervical canal into the vagina; these are referred to as nascent leiomyomas. The standard surgical treatment is transvaginal myomectomy, although hysteroscopic management may be required when complete removal of the pedicle base cannot be safely achieved by the vaginal route alone. We report the case of a 36-year-old nulligravid woman presenting with hypermenorrhea, pelvic pain, and fatigue, in whom a large prolapsed pedunculated submucous leiomyoma measuring 8 × 8 × 7 cm was managed using a hybrid approach. The prolapsed mass was first removed transvaginally, and the residual pedicle base was subsequently resected by operative hysteroscopy using a bipolar system. Histopathological examination confirmed a leiomyoma with degenerative changes. Postoperative recovery was uneventful, and follow-up transvaginal ultrasonography at 1, 3, and 6 months showed no gynecological abnormality. The patient also reported resolution of symptoms and improvement in menstrual pattern during follow-up. This case highlights that, in selected patients with large prolapsed pedunculated submucous leiomyomas, a hybrid approach combining transvaginal myomectomy with operative hysteroscopic pedicle resection may facilitate complete removal while preserving the uterus and minimizing surgical morbidity.